Mammal activity patterns around the Camisea natural gas transportation pipeline in the Machiguenga Communal Reserve, Cusco, Peru - Zegarra, Orlando (2023)
The present study investigates the hourly activity patterns of mammals inhabiting the area surrounding the Camisea gas pipeline that crosses the Machiguenga Communal Reserve. From February 2020 to January 2021, a photographic record was conducted using camera traps placed along the gas pipeline. Activity patterns were estimated using Kernel density functions. During the study period, 25 mammal species were recorded. It was found that Dasyprocta kalinowskii and Eira barbara exhibit a diurnal activity pattern, whereas Cuniculus paca, Tapirus terrestris, Dasypus spp., and Mazama spp. display predominantly nocturnal behavior. It is suggested that observed activity patterns could be influenced by various factors such as competitive exclusion between D. kalinowskii and C. paca, seasonal food availability for T. terrestris, temperature and precipitation variations for Dasypus spp., phylogenetic constraints in Mazama spp., and temporal segregation with other carnivores for E. barbara. The significance of collaboration between energy industry companies, native communities, and governmental organizations is emphasized.